2022
DOI: 10.2196/31533
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Networks in the Context of the Dietitian’s Practice in Brazil and Changes During the COVID-19 Pandemic: Exploratory Study

Abstract: Background Social networks have been pointed out as 1 of the greatest means of spreading information. A large part of the population is already present on these platforms, looking up subjects such as health, nutrition, and food. To reach this audience, it may be important for dietitians to explore social networks. However, there is a gap in scientific studies on exploring the ways in which these platforms are used by dietitians in Brazil, and the roles they play in the profession have not been well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 19 publications
(21 reference statements)
3
14
0
Order By: Relevance
“…Approximately 60% of the dietitians used social media for their work, which aligns with findings from previous studies, where the professional social media usage among dietitians has been ranged from 38% 13 to around 90%. 5,7 Dietitians highlighted several key professional benefits of using social media, including monitoring the nutrition field, sharing information and interacting and networking with colleagues. These reasons have also been commonly reported in previous studies examining dietitians' social media use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 60% of the dietitians used social media for their work, which aligns with findings from previous studies, where the professional social media usage among dietitians has been ranged from 38% 13 to around 90%. 5,7 Dietitians highlighted several key professional benefits of using social media, including monitoring the nutrition field, sharing information and interacting and networking with colleagues. These reasons have also been commonly reported in previous studies examining dietitians' social media use.…”
Section: Discussionmentioning
confidence: 99%
“…We formulated the questions based on previous studies to describe the use of social media in the profession of registered dietitians. 2,5,7,13 Additionally, we created a few more questions to explore dietitians' social media skills and factors influencing their social media use. The survey consisted of a mixture of structured multiple-choice questions (including Likertscale questions) and open-ended questions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rising popularity of Instagram offers a new opportunity to deliver health promotion programs at a relatively low cost. A survey conducted in Brazilian dietitians identified that Instagram was the most popular social networking site and was commonly used to generate content related to food and nutrition [ 16 ]. Instagram has been previously used to implement a social media campaign promotion for healthy eating during the COVID-19 pandemic in Canada [ 17 ] and delivered an exercise program in Australian females aged 18–30 years [ 18 ].…”
Section: Introductionmentioning
confidence: 99%